HR-LCMS based metabolites profiling, pharmacognostic study, and antimycotic activity of leaves of Ruellia asperula - Patel, Arshu; Kudnar, J R; Jadhav, R S; Ghuge, B (Journal of Applied Pharmaceutical Research, 2025)
Background: Fungal infections pose a global health challenge, exacerbated by rising drug resistance and immunocompromised populations. Ruellia asperula, a traditional medicinal plant, has garnered attention for its bioactive compounds, including flavonoids and alkaloids. This study aims to profile its metabolites using HR-LCMS and evaluate its antimycotic potential, contributing to the discovery of natural therapeutic agents. Methodology: Leaves and bark of Ruellia asperula were collected, authenticated, and processed for analysis. Physicochemical standards like moisture content, ash values, and extractive yields were determined. Preliminary phytochemical screening identified bioactive compounds. Ethanolic extracts were prepared via Soxhlet extraction, fractionated through column chromatography, and analyzed using HR-LCMS. In vitro, antimycotic assays were conducted against Alternaria and Macrophomia. Results: Physicochemical analysis revealed a total ash content of 2.87% w/w, water-soluble ash of 25.78% w/w, and alcohol-soluble extractive value of 9.53% w/w, indicating substantial secondary metabolites. Phytochemical screening identified alkaloids, flavonoids, and saponins. HR-LCMS analysis detected 18 compounds in the ethanolic fraction and 13 in the chloroform fraction. In vitro assays demonstrated significant inhibition of Alternaria and Macrophomia, with activity comparable to Itraconazole. Discussion: Ruellia asperula leaves demonstrated high phytochemical quality and are rich in flavonoids and alkaloids. HR-LCMS profiling identified bioactive metabolites, while in vitro tests confirmed significant antifungal activity. These findings underscore the plant's potential as a natural antimycotic agent. Conclusion: This study highlights the phytochemical richness of Ruellia asperula, confirmed by HR-LCMS and pharmacognostic analyses. Its potent antimycotic activity, comparable to Itraconazole, positions it as a promising candidate for natural fungal therapies